Texture evolution and anisotropy of TA18 titanium alloy strip under rolling and heat treatment conditions - Bobo Li; Jiangkun Fan; Wenyuan Zhang; Jiaxing Zhao; Ding Zhao; Huifa Tao; Xiaobo Hao; Fei Wang; Peng Jiang; Hongchao Kou; Jinshan Li (Journal of Materials Research and Technology)
Texture and anisotropy control of rolled strip have always been a technical problem in titanium alloy industry, especially for near-alpha titanium alloys. In order to solve the above problems, we innovatively propose a process method for efficiently preparing weakly anisotropic alloy strips. In this paper, the texture evolution and anisotropy of TA18 titanium alloy strip under various rolling and heat treatment conditions were systematically studied by EBSD and other technical means. The results have showed that the hot-rolled TA18 titanium alloy has a distinct band microstructure along the RD. The obvious tensile properties anisotropy of hot-rolled TA18 titanium alloy is mainly due to the non-uniform microstructure formed and strong T-type micro-texture. The hot-rolled TA18 titanium alloy after 700 °C/3h heat treatment occurred complete recrystallization process, which formed the fine and uniform equiaxed grains. Texture components distribution of the titanium alloy changed from typical bimodal texture to the tendency of <0001>//normal direction (ND) base plane texture. The hot-rolled TA18 titanium alloy after heat treatment at 700 °C/3h, followed by rolling to 4.8 mm at room temperature and annealing at 730 °C/1h, could effectively reduce the anisotropy of titanium alloys. Finally, the formation of anisotropy of yield strength was considered as the different slip activation behaviors due to the influence of micro-texture orientation. This study innovatively proposes an efficient method for fabricating alloy strips with reduced anisotropy forTA18 titanium alloy strips.